Mus-E: experiencia inclusiva favorecedora del éxito educativo en Centros de Atención Educativa Preferente - Rincón Asensio, Montserrat (Revista Española de Educación Comparada, 2025)
Within the Network of Preferential Educational Attention Centers (CAEP) of Extremadura there are 24 Educational Centers that are in disadvantaged socio-cultural contexts and whose students belong, in a high proportion, to various groups at risk of social exclusion. Among these groups are ethnic minorities, immigrant, students with a high rate of school absenteeism, and generally, with a specific need for educational support. The objective of the research is to establish to what extent the educational centers that implemented the Mus-E Program in the Early Childhood and Primary Education Centers of Extremadura with a CAEP profile influenced the educational success of the students and the reduction of school absenteeism and determine to what extent it is a tool for educational and social transformation. Under the Comparative Education methodology, 20 Early Childhood and Primary Education Centers (CEIP) that shared similar characteristics in terms of school students, family, educational context, and sociocultural environment were analyzed. All of them are pioneer Centers in the use of innovative methodologies, but only 50% of them use the Mus-E methodology. In the study, evidence was found of significant differences in educational success and/or promotion rates over the three academic years analyzed, which allowed us to deduce that in the educational centers where the Mus-E Program is implemented, academic results are better than in the other educational centers. This allowed us to open new lines of research on the importance of using active methodologies as indicators of educational success in the most disadvantaged school population.